In silico ADME/T prediction of novel potential inhibitors against dengue virus (Research, Society and Development, 2021)
Dengue is an emerging disease with a major impact on public health, with millions of viral infections occurring annually, for which there is still no effective therapy. The present study aims to predict the physicochemical, pharmacokinetic and toxicological properties of candidates for drugs against dengue. 17 candidates for anti-dengue drugs were developed on the PubChem Sketcher V. 2.4® platform. The physical-chemical parameters were quantified on the Molinspiration® platform. Subsequently, the pharmacokinetic parameters were measured using the SwissADME® tool. Finally, the OSIRIS Property Explorer® platform was used to determine the toxicological effect of anti-dengue candidates. Compounds 8 and 14 did not violate any of the rules instituted by Lipinski. All other compounds showed more than one violation, with compounds 5, 7 and 9-11 showing up to 3 violations. As for the pharmacokinetic evaluation, of the compounds designed here only compounds 13 and 14 showed high gastrointestinal absorption. Compounds 2, 15 and 17 have at least a high-risk score for one of the toxicity factors for mutagenesis, tumorigenesis, irritating and reproductive effects. Compounds 1-4 have at least an intermediate risk score for one of the toxicity factors. All other compounds have low risk scores for one of the toxicity factors. The in silico prediction made in that study indicated that compounds 13 and 14 are the most promising for being possible anti-dengue candidates and useful for future screening in tests performed on cells and animals.